Nakagawa, Dave (audio interview #2 of 2) - Nakagawa, Dave; Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This second, more comprehensive interview with Dave Nakagawa was conducted some twenty six years after the initial very short and technically flawed interview done by an Asian American Studies class. Nakagawa was a very gracious host, and his memory remained sharp and clear. TOPICS - family background and history; housing arrangements; relationship with canneries; fishing practices;childhood activities; judo classes; community composition and geography; Japanese baths; diet; and his mother's work at cannery;Japanese celebrations; reputation of Terminal Islanders among other Japanese; Little Tokyo; athletic ability; weight lifting; high school athletics;activities and experiences at San Pedro High School; rumor of his being a spy; dating; FBI round-up of fishermen; evacuation and internment;beginning of youth work; military service; return to Los Angeles; youth work in Boys Club and YMCA;post-war youth work; marrieage; joining Presbyerian Church; Terminal Island's switch from Baptist to Presbyterian Church; father's resumption of fishing; reflections on life on Terminal Island; 11/8/2001